SYSTEMATIC LITERATURE REVIEW: POLITICAL PATRONAGE VERSUS MERIT SYSTEM ON LOCAL GOVERNMENT ANALYSIS VOSVIEWER - Handayani, Sri; Fadzia Fauzi, Ella; Dwi S.N, Risnu; Damayanti, Khusna (Journal of Governance Innovation, 2024)
It is important to improve the public sector with recruitment rules that aim to improve public services by minimising political interests and patronage practices. The purpose of this study is to examine the development of the application of the merit system in the prevention of patronage practices in local government. Bibliometric analysis using VOSViewer. The literature review in this study provides an overview of the improvement of the public sector from the perspective of the merit system, taking articles in the period 2013-2023. The results obtained in this study are the prevention of patronage practices with the merit system in local government administration successfully implemented in Indonesia, namely in the cities of Medan, Deli Serdang and DIY, while in other countries it was successfully implemented in the African state of Nigeria, the merit system is used to prevent political patronage in the public sector by ensuring the acceptance of competent employee candidates, and reducing the influence of political patronage that previously hindered the development of public services and justice.